Occupational chemicals exposure and related hematological consequences among automobile garage workers in Benghazi, Libya. - Shaboun, Seham; Alzunni , Faisa (Libyan Journal of Science &Technology, 2025)
Background: The automobile repair garage workers are exposed as part of their occupation to aromatic hydrocarbons, aliphatic hydrocarbons, and petrochemicals that have adverse effects on the heath of the human being. In Libya, there were no studies on the type and level of exposure to chemicals among automobile workers in different garage workplaces. Therefore, this field study was aimed to determine the consequences of occupational chemicals exposure on the hematological parameters of automobile workers. Methods: In this comparative cross-sectional study, a total of 70 participants were enrolled, a number of 35 automobile repair garage workers filled out a questionnaire and gave blood samples for complete blood count (CBC) test and compared with an equal number of 35 control groups of the same sex and age group, gave also blood samples for CBC test. The data from the filled questionnaire were coded and the blood tests results were entered into the SPSS program (version 21). The data was presented by descriptive statistics. Meanwhile, the statistical analysis was done using the independent sample t-test. In addition, the proportions of categorical variables were compared using the Chi-square test. Results: Our findings in comparison to control showed that there was no significant difference in the RBC count of all participants. Both petrochemicals and oils exposed groups had higher MCV levels with statistically significant differences of p=0.05 and p=0.006 respectively. Whereas, the MCHC was significantly increased in petrochemicals and oil exposed groups (p=0.027 and p=0.008 respectively), moreover, the total WBC counts were significantly reduced in paints exposed workers (p=0.04), while no significant changes in petrochemicals and oils exposed groups (p=0.450 and p=0.359 respectively). Additionally, both petroleum and oil exposed were anemic in comparison to the normal reference value of hemoglobin level. Conclusion: Our results indicated that working in the garage changes some of the hematological parameters of the workers. Thus, suitable and actual safety guidelines should be implemented to prevent possible chemical exposure during routine work, and further study on the type of heavy metals causing these hematological changes should be conducted in further studies.